Railway track tracer system for creature detection. Issue 1 (February 2021) - Deepa, M; Raji, C G; Ajina, VA; Ashla,; Azra, Afsal; Susanna, George
Abstract: Railway Track Tracer System for creature detection is a system for detecting creatures on the railway tracks. This system will help to avoid many accidents that occur on rails. This system mainly focuses on some areas where creatures are always seen on the railway tracks. In some areas, elephants are crossing the railway tracks frequently. This system frequently monitors the railway tracks using a camera, so that the presence of creatures can be easily identified and then necessary actions can be taken to prevent accidents. The system includes a camera, train status system and an application for alert. The camera captures the images on the track at each interval of time and then through image processing the captured image will be recognized. If an object is identified on the track, then immediately an alert message will be sent to the nearby control room and loco-pilot. This system will be helpful for the society to prevent accidents due to creatures on the railway tracks.